The effects of thermal acclimation on lethal temperatures and critical thermal limits in the green vegetable bug, Nezara viridula (L.) (Hemiptera: Pentatomidae) - Chanthy, Pol; Martin, Robert J.; Gunning, Robin V.; Andrew, Nigel (Frontiers in Physiology, 2012)
According to geographical distribution, Nezara viridula (Heteroptera: Pentatomidae) can be found across tropical, subtropical and temperate regions and this pattern is assumed to reflect differences in thermal adaptation, particularly in cold tolerance. Here the lethal temperature and critical thermal limits (thermal tolerance) are examined for N. viridula. The upper lethal temperature for N. viridula at two contrasting climate locations (Breeza and Grafton, New South Wales, Australia) was 40.3ºC with 20% survival under the stress of high temperature. The lower lethal temperature did not differ between these two populations and was -8.0ºC with 20% survival under low temperature stress. Survival of N. viridula increased after acclimation at high temperature for seven days. In contrast, when acclimated at lower temperatures (10 and 15ºC), survival of Breeza and Grafton N. viridula was lower than 20% at -8.0ºC. Control-reared N. viridula adults (25ºC) had a mean CTMinOnset (cold stupor) of 1.3 ± 2.1ºC and a mean CTMax (heat coma) of 45.9 ± 0.9ºC. After 7 days of acclimation at 10, 20, 30, or 35ºC, N. viridula adults exhibited a 1ºC change in CTMax and a 1.5ºC change in CTMinOnset. CTMax and CTMinOnset of Breeza and Grafton N. viridula populations did not differ across acclimation temperatures. These results suggest that short-term temperature acclimation is more important than provenance for determining lethal temperatures and critical thermal limits in N. viridula.